Peran Copywriter dalam Pembuatan Kampanye Iklan “Jakarta 101” Wisata Lokal di Jakarta - Rayhan Amelia Putri; Rizky Fauzi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Investment encouragement is needed in the tourism sector involving participation from the community, businesses, as well as local and central governments. This collaboration is crucial to ensure a shared commitment to developing the tourism potential with sustainable growth and positive impact. The